Kajian Awal Pemanenan Siput Laut (Gastropoda) di Pantai Krakal, Yogyakarta: II. Aktivitas Pemanen - Felicia Zahida; Mastok B. Sinulingga; Wibowo N. Jati (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2005)
A preliminary study on marine snails harvest (Gastropods) has been done in Krakal beach, Yogyakarta, during October to December 2003. Krakal beach has become an under-pressure habitat since tourism industry occurred all over Indonesia. Marine snails have been harvested for over two decade in this area but there is no study regarding this activity yet. This study aims to elucidate the harvester’s knowledge about simple conservation and activities such as the way of harvesting, the intensity of harvesting and the income generating from harvesting gastropods.